Answer:
1 2⋅−1⋅3 5=4 5
Step-by-step explanation:
Combine multiplied terms into a single fraction
12y−1⋅35=45
\frac{1}{2}y-1 \cdot \frac{3}{5}=\frac{4}{5}
21y−1⋅53=54
12−1⋅35=45
Answer:
Step-by-step explanation:
Answer:
x=9 output 1=20.25
Output 2 equals 27
Step-by-step explanation:
This function is constant, so you do input times 2.25 for each.
The box below 6 is 9 because we are counting by 3
9 x 2.25=20.25
12 x 2.25=27
Hope this helped :)
Answer:
Your correct, it's C and D
Step-by-step explanation:
A and E are right triangles, so that's not the answer. B and F are isosceles triangles so that's not the answer. C and D are 2 DIFFERENT obtuse triangles so that's why C and D are the answers.
Answer:
The change in elevation=2,400 feet
Step-by-step explanation:
The expression to determine the change in elevation after 6 minutes is a s follows;
D=S×T
where;
D=change in elevation in feet
S=speed/ descending rate
T=time
In our case;
D=unknown
S=400 feet/minute
T=6 minutes
replacing;
D=400×6=2,400 feet
The change in elevation=2,400 feet